THE EFFECTS OF IMMERSIVE MULTIMEDIA LEARNING WITH PEER SUPPORT ON VOCABULARY, GRAMMAR, AND MOTIVATION - Asnawi Muslem; Yulianti Yulianti (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
This study investigated the effects of the immersive multimedia learning technique with peer support on performance in English in terms of vocabulary, grammar, and motivation. The quasi-experimental design with pre-test and post-test was employed for the study. The first factor was the strategy of learning, namely the use of immersive multimedia learning with and without peer support, while the second factors comprised achievement in English. 80 first-year university students enrolled in an English as a foreign language course were selected for this study and the treatment lasted for eight weeks. Data were analysed using one-way ANOVA. The findings showed that there were no significant differences in performance for vocabulary, grammar, and motivation between the students who engaged with and without peer support groups. It can be concluded that the use of immersive multimedia learning with and without peer support groups improve their motivation but did not significantly improve their vocabulary and grammar.